A comparative analysis of the study of hadith science in the hadith schools of Mawarounnahr and al-Azhar (Texas Journal of Multidisciplinary Studies, 2021)
In the study of hadith sciences, a comparative analysis of the methods of the two schools of hadith schools, namely Movarounnahr and al-Azhar, was made. In the process of analysis, evidence was presented on the basis of historical and scientific sources. The differences and interrelationships between schools on these methods were also highlighted